Exploring the leadership behaviors of millennial community leaders during the pandemic: The Case of the Science City of Muñoz in the Philippines - Olive Chester M. Cuya-Antonio; Arneil G. Gabriel; Corinthian M. Obispo; Feliciana P. Jacoba; Sanjay P. Claudio (Masyarakat, Kebudayaan dan Politik, 2022)
Millennials are those born between the late 1980s and late 1990s. They are individuals who are comfortable in the use of technology giving them competitive advantage in the global workforce. Surprisingly, despite their significant number in the workforce, there is a dearth of study on millennial leadership styles. This study examines the millennial community leaders in the Philippines during the COVID-19 pandemic. It employed exploratory descriptive-qualitative research method. Sixteen millennial community leaders in the Science City of Muñoz in the Philippines and twelve citizens and subordinates participated in the study. The basis of analysis is the Responsible Leadership for Performance framework. The findings showed that responsibility and accountability to their tasks and functions are common traits of millennial community leaders during pandemic. They are perceived to possess attributes such as: people-centered, honest, reliable, just, approachable, responsible, affirmative, pure-hearted, and hardworking during pandemic. The study confirmed that millennials’ technological inclination, their ideals and aspirations are shaped by their socio-historical background. Though lacking of experience and resources, they compensate it with strong mind and heart to lead the community in its response to pandemic emergencies.